Effect of selenium in soil on the toxicity and uptake of arsenic in rice plant. (January 2020) - Pokhrel, Ganga Raj; Wang, Kai Teng; Zhuang, HongMao; Wu, YongChen; Chen, Wei; Lan, Yan; Zhu, Xi; Li, Zhong; Fu, FengFu; Yang, GuiDi
Abstract: Selenium can regulate arsenic toxicity by strengthening antioxidant potential, but the antagonism between selenite or selenate nutrient and the translocation of arsenic species from paddy soil to different rice organs are poorly understood. In this study, a pot experiment was designed to investigate the effect of selenite or selenate on arsenite or arsenate toxicity to two indica rice cultivars (namely Ming Hui 63 and Lu You Ming Zhan), and the uptake and transportation of arsenic species from paddy soil to different rice organs. The results showed that selenite or selenate could significantly decrease the arsenate concentration in pore water of soils, and thus inhibited arsenate uptake by rice roots. However, the existence of selenite or selenate didn't decrease arsenate concentration in rhizosphere pore water of two indica rice cultivars. There existed good antagonistic effect between selenite or selenate and the uptake of arsenite and arsenate in rice plant in the case of low arsenic paddy soil. However, this antagonism depended on rice cultivars, arsenic species and arsenic level in soil. There existed both synergistic and inhibiting effects between the addition of selenite or selenate and the uptake of trimethylarsinoxide and dimethylarsinic acid by two indica rice cultivars, but the mechanism was unclear. Both selenite and selenate are all effective to decrease the translocation of inorganic arsenic from the roots to their above-ground rice organs in arsenite/arsenate-spiked paddy soil, but selenate had stronger inhibiting effect on their transfer factors than selenite. Highlights: Selenite and selenate are found to facilitate the arsenate adsorption by paddy soil. Selenite and selenate inhibited the uptake of arsenate by rice roots. Antagonism between Se and As depended on rice cultivar, As species and concentration. Selenate has stronger inhibition on inorganic arsenic transfer factors than selenite. Selenium has synergistic and inhibiting effects on TMAO(V) and DMA(V).